Cross-cultural adaptation, reliability, and validity of the Turkish version of moral courage scale for physicians - Şerife Yılmaz; Gamze Özbek Güven; Feyza İnceoğlu (PLoS ONE, 2025)
Aim Physicians, like other healthcare professionals, frequently encounter situations requiring moral courage in their professional lives. However, studies on the moral courage of physicians are limited in the literature. This study aims to evaluate the Turkish adaptation, validity, and reliability of the Moral Courage Scale for Physicians (MCSP) and to contribute to national and international studies on moral courage among physicians. Materials and methods This methodological study involved the adaptation, validation, and reliability assessment of the MCSP in Turkish. The scale’s internal consistency was evaluated using Cronbach’s α coefficient, and the total correlation coefficients for the items were calculated. Test-retest reliability was assessed using a two-group design. Results The Turkish version of the MCSP demonstrated high internal consistency, with a Cronbach’s α coefficient of 0.91. The total correlation coefficients for the items ranged from 0.387 to 0.797. A significant positive correlation was found between the test and retest scores of the MCSP (p < 0.05). Conclusion The Turkish version of the MCSP is a valid and reliable tool for assessing moral courage among physicians.